ANALISIS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS 5 SDN 2 TAMBAKRIGADUNG - Rizka Rismawanda; Retno Dwi Pratiwi; Novi Verdiana Nisa Haryanti; Yuana Sovia Rini; Humairah Humairah (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2023)
In the era of world progress, the world of education has also experienced significant developments. One of them is now in several learning activities many teachers are already using video as a learning medium. Learning media is considered very important because it is one of the assistants in teaching activities. This video-shaped media helps teachers explain material to students. In addition to increasing interest in learning, students are also more enthusiastic because of the visuals in a video. Learning media can also be one of the factors that trigger students' interest in learning. Interest in learning is an inner urge to do something that can make him interested and happy. The research method used is descriptive qualitative. The purpose of this research is to analyze learning activities at SDN 2 Tambakrigadung. Precisely in grade 5 with a total of 30 students. The results obtained in this study showed that the activeness of students in voicing their opinions increased by 20% after the researchers explained the material presented using learning media in the form of videos.